2007
DOI: 10.1002/esp.1492
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for non‐destructive field measurement of rock‐surface strength: an application of the Equotip hardness tester to weathering studies

Abstract: Tafone-like depressions have developed on the Aoshima sandstone blocks used for a masonry bridge pier in the coastal spray zone. A thin layer of partial granular disintegration was found on the surface in depressions. To evaluate quantitatively the strength of the thin weathered layer, the hardness was measured at the surface of the sandstone blocks using both an Equotip hardness tester and an L-type Schmidt hammer. Comparison of the two testing results indicates that the Equotip hardness value is more sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 18 publications
3
88
0
1
Order By: Relevance
“…If coastal rocks are weathered, then we must replace S c in equation (5) with reduced strength owing to weathering. The strength of rocks subjected to weathering has been measured by many researchers using Schmidt hammers (references cited in Aoki & Matsukura 2007). Weathering of a coastal rock mass without discontinuities begins at the rock surface and penetrates into the interior with time, which results in the formation of strength gradient, that is, weathering profile, with the weakest part being located at the surface forming a thin layer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If coastal rocks are weathered, then we must replace S c in equation (5) with reduced strength owing to weathering. The strength of rocks subjected to weathering has been measured by many researchers using Schmidt hammers (references cited in Aoki & Matsukura 2007). Weathering of a coastal rock mass without discontinuities begins at the rock surface and penetrates into the interior with time, which results in the formation of strength gradient, that is, weathering profile, with the weakest part being located at the surface forming a thin layer.…”
Section: Discussionmentioning
confidence: 99%
“…Weathering of a coastal rock mass without discontinuities begins at the rock surface and penetrates into the interior with time, which results in the formation of strength gradient, that is, weathering profile, with the weakest part being located at the surface forming a thin layer. For testing this thin weathered layer a Schmidt hammer is not a suitable device (Aoki & Matsukura 2007), rather an Equotip hardness tester or a needle-type penetrometer is used. Using the Equotip tester, Aoki & Matsukura (2007) investigated weathering-induced strength reduction of sandstone blocks used for a masonry bridge pier at Aoshima, described before, and reported that the surface strength of the blocks located in the inter-to supratidal environment reduced to c. 70% of that of fresh blocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However SHRT should be treated only as a preliminary reconnaissance and the study on influence of coastal processes on rock breakdown in polar climates should be supported by application of more advanced methods (e.g. Equotip, MEM, Terrestrial Laser Scanning, digital photogrammetry, GIS modelling) to re− duce the risk of misinterpretation (Lim et al 2005(Lim et al , 2010Aoki and Matsukura 2007;Viles et al 2011). The major weakness of this study is above all the lack of information regarding the spatial distribution of permafrost and the difference in development of the active layer between coastal and inland outcrops, which could have a significant impact on rock stability and degree of weathering.…”
Section: Discussionmentioning
confidence: 99%